Chromosome-level Genome Assembly and Sex-specific Differential Transcriptome of the White-backed Planthopper, Sogatella furcifera - Ye, Yu-Xuan; Li, Dan-Ting; Zhang, Si-Yu; Shen, Zhi-Cheng; Zhang, Chuan-Xi (Current genomics, 2023)
Background: The white-backed planthopper (WBPH), Sogatella furcifera, causes great damage to many crops (mainly rice) by direct feeding or transmitting plant viruses. The previous genome assembly was generated by second-generation sequencing technologies, with a contig N50 of only 51.5 kb, and contained a lot of heterozygous sequences. Methods: We utilized third-generation sequencing technologies and Hi-C data to generate a highquality chromosome-level assembly. We also provide a large amount of transcriptome data for fulllength transcriptome analysis and gender differential expression analysis. Results: The final assembly comprised 56.38 Mb, with a contig N50 of 2.20 Mb and a scaffold N50 of 45.25 Mb. Fourteen autosomes and one X chromosome were identified. More than 99.5% of the assembled bases located on the 15 chromosomes. 95.9% of the complete BUSCO Hemiptera genes were detected in the final assembly and 16,880 genes were annotated. 722 genes were relatively highly expressed in males, while 60 in the females. Conclusion: The integrated genome, definite sex chromosomes, comprehensive transcriptome profiles, high efficiency of RNA interference and short life cycle substantially made WBPH an efficient research object for functional genomics.